2020
DOI: 10.1101/2020.03.26.009514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forced Abstinence from Alcohol Induces Sex-Specific Depression-like Behavioral and Neural Adaptations in Somatostatin Neurons in Cortical and Amygdalar Regions

Abstract: 251 words Main Text: 6367 words Figures: 6 Dao et al. Forced Abstinence in Cortico-Amygdalar Regions 2 ABSTRACT Forced abstinence (FA) from alcohol has been shown to produce a variety of anxiety-and depression-like symptoms in animal models. Somatostatin (SST) neurons, a subtype of GABAergic neurons found throughout the brain, are a novel neural target with potential treatment implications in affective disorders, yet their role in alcohol use disorders (AUD) remains to be explored. Here, we examined the neuroa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
2
1
Order By: Relevance
“…We previously reported that PL SST neurons are hyperexcitable following prolonged withdrawal from alcohol drinking (> 4 weeks) in a 2-bottle choice model (34), which contrasts with the hypoexcitable state in acute withdrawal (24-h) from DID observed here. It should be noted that the excitability recording in the former report was done following an acute stressor (forced swim).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We previously reported that PL SST neurons are hyperexcitable following prolonged withdrawal from alcohol drinking (> 4 weeks) in a 2-bottle choice model (34), which contrasts with the hypoexcitable state in acute withdrawal (24-h) from DID observed here. It should be noted that the excitability recording in the former report was done following an acute stressor (forced swim).…”
Section: Discussioncontrasting
confidence: 90%
“…Whole cell voltage clamp and current clamp recordings were conducted in the PL similarly to those previously published (spontaneous excitatory and inhibitory postsynaptic currents, sEPSCs and sIPSCs respectivelu, and intrinsic excitability(20,21,34); confirmation of DREADD expression and function (30)). The PL was identified according to the Allen Mouse Brain Atlas.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess whether a lesion of the cholinergic neurons in the HDB produces depressive-like behavior and FLX or ketamine inhibits such depressive-like behavior, three sets of experiments were conducted according to the following experimental design. The sequence of the behavioral tests was described in previous studies with minor modifications ( Cutuli et al, 2013 ; Ke et al, 2019 ; Dao et al, 2020 ). Experiment 1 ( Figure 3A ): Rats were randomly divided into three groups ( n = 10 rats per group): non-operated (Control), sham operated (Sham) and 192 IgG-saporin injection (Ig-saporin).…”
Section: Methodsmentioning
confidence: 99%